1961
DOI: 10.1139/b61-078
|View full text |Cite
|
Sign up to set email alerts
|

The Botany of the Northwestern Queen Elizabeth Islands

Abstract: Ellef Ringnes Island has a confirmed flora of 49 vascular plants and five parasitic fungi. The adjacent islands have less diversity of habitat and probably have even poorer floras. There are no endemics and the plants are extremely depauperate. The summer climate at Isachsen is colder than at any other station in the Canadian arctic. Although there are no convincing indications that Ellef Ringnes I. was overrun by a Wisconsin continental ice sheet, it cannot have escaped being snow-covered. The light cover of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1965
1965
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 6 publications
0
40
0
Order By: Relevance
“…Since Savile (1961) used mostly qualitative characters to distinguish the three groups, further analyses based on both qualitative and quantitative characters and including more western montane and eastern arctic specimens should be made to further test his hypothesis.…”
Section: Geographical Variation In Saxifraga Tenuismentioning
confidence: 99%
See 1 more Smart Citation
“…Since Savile (1961) used mostly qualitative characters to distinguish the three groups, further analyses based on both qualitative and quantitative characters and including more western montane and eastern arctic specimens should be made to further test his hypothesis.…”
Section: Geographical Variation In Saxifraga Tenuismentioning
confidence: 99%
“…In addition Polunin (1959) suggested that hybridization may also occur between the S. nivalis complex and other closely related species, such as S. hieracifolia. Savile (1961) proposed that North American S. tenuis may be divided into three disjunct and morphologically distinct "populations." The first is a high arctic population composed of plants identical to material from the north of Greenland and hypothesized to have spread from there following the Pleistocene.…”
mentioning
confidence: 99%
“…Floristic exploration has continued apace (e&, Hale, 1954;Schofield and Cody, 1955;Savile, 1959Savile, , 1961Savile, , 1963Beschel, 1961;Bursa, 1961Bursa, , 1963Booth and Barrett, 1971;Brassard, 1972;Mason et al, 1972;Barrett and Teeri, 1973;Kuc, 1974;Schulten, 1975;Barrett and Thomson, 1975;Brassard et al, 1979;Ritchie, 1984;Kojima and Brooke, 1985;Brooke and Kojima, 1985;Soper and Powell, 1985). There are now many descriptions and analyses of plant communities (e&, Savile, 1959;Johnson, 1969;Larsen, 1972Larsen, , 1973Forest Management Institute, 1974;Muc and Bliss, 1977;Hsiao, 1980;Thompson, 1980;Bliss and Svoboda, 1984;Bliss et al, 1984;Soper and Powell, 1985).…”
Section: Achievementsmentioning
confidence: 99%
“…A CC UMULATION In 1960In , 1961 and 1962 th e win ter's snow accumu lation was measured at each stake before the melt season began (F ig. 4) .…”
Section: E P T H Fro M Grav Ity O Bse R Vat Ionsmentioning
confidence: 99%
“…Ice rafting is a possible explanation of the occurrence of erratic boulders over much of the area. Savile ( 1961 ) has pointed out that, because of the poor flora and the low summer temperatures presently experienced in the area, it could hardly have been without a permanent snow cover with a general lowering of temperature, even allowing for the very scanty precipitation prevailing in these islands. This discussion gives added interest to the state of the small ice cap on Meighen Island.…”
Section: '1 Introductionmentioning
confidence: 99%